Fruity Popsicles / Siti Khadijah Mohtar ... [et al.] - Mohtar, Siti Khadijah; Muhammad Fuad Tiew, Nur Nadira Ashyikin; Mohd Shah, Siti Aisyah; Muhammad Lotffi, Batrisyia; Abd Wahid, Siti Nabilah; Vince Rabing, Jesse; Ahmad Padzil, Nurul Fatinah (2015)
1.1 Name of company Our company name is Fruity Popsicles which will serve you a healthy digestive ice cream that have a lot of flavor consist of nutrients, vitamin, fiber and calcium.